Sociolinguistics Background Determining Linguistic Politeness - Shokhikhatul Khasanah (Alsuna: Journal of Arabic and English Language, 2019)
This article is intended to show that Sociolinguistics background influences linguistic behavior among people. The way people communicate with other is vary based on their Sociolinguistics background; included the way to show Politeness. Thus, the difference Sociolinguistics background will determine the linguistic Politeness. Politeness is a concept which seeks to give respect to other when we are speaking. Some Sociolinguistics backgrounds that determine Linguistic Politeness, such as: power relationship and social distance, education, social status, job profession, gender, and ethnicity